• Non ci sono risultati.

# such that whenever x, y ≥ 0

N/A
N/A
Protected

Condividi "such that whenever x, y ≥ 0"

Copied!
1
0
0

Testo completo

(1)

Problem 11835

(American Mathematical Monthly, Vol.122, April 2015) Proposed by G. Stoica (Canada).

Find all functions f from [0, ∞) to [0, ∞) such that whenever x, y ≥ 0,

3f (2x) + 5f (2y) ≤ 2f (√

3x + 5y).

Solution proposed by Moubinool Omarjee, Lyc´ee Henri IV, Paris, France, and Roberto Tauraso, Dipartimento di Matematica, Universit`a di Roma “Tor Vergata”, Italy.

We will show a more general statement.

Let a ∈ (0, 1) and b ∈ (1, +∞) such that ambn6= 1 for all n, m ∈ N+.

If f : [0, ∞) → [0, ∞) is a function such that whenever x, y ≥ 0, af (x) + bf (y) ≤ f (ax + by), then f (t) = ct for some c ∈ [0, +∞).

The solution to the proposed problem is obtained when a =√

3/2 and b = 5/2.

We divide the proof into several step.

i) The set S := {ambn : m, n ∈ N} is dense in [0, +∞).

It follows from the fact that the set {logb(ambn) : m, n ∈ N} is dense in R. In fact logb(ambn) = n − m logb(1/a) = n − bmαc − {mα},

where α = logb(1/a) is a positive irrational number (otherwise there would be p, q ∈ N+ such that 1/a = bp/q, that is aqbp= 1). It suffices to note that {{mα} : m ∈ N} is dense in [0, 1].

ii) f (0) = 0.

Let x = y = 0, then (a + b − 1)f (0) = af (0) + bf (0) − f (a0 + b0) ≤ 0 which implies that f (0) = 0 because f (0) ≥ 0 and a + b > b > 1.

iii) For s ∈ S, and t ≥ 0, sf (t) ≤ f (st).

By definition s = ambn for some m, n ∈ N. If m = n = 0 then s = 1 and the inequality is trivial. Moreover, by the inductive assumption,

ambn+1f (t) ≤ bf (ambnt) ≤ af (0) + bf (ambnt) ≤ f (a0 + b(ambnt)) = f (ambn+1t).

In a similar way,

am+1bnf (t) ≤ af (ambnt) ≤ af (ambnt) + bf (0) ≤ f (a(ambnt) + b0) = f (am+1bnt).

iv) For all t ≥ 0, f (t) ≤ f (1)t.

By ii), it holds for t = 0. Let t > 0, then by i) there exists a sequence {sk}k≥0in S such that sk → (1/(bt)). Hence, by iii),

f (t) ≤ f (skt) sk

= bf (skt) bsk

≤ af (xk) + bf (skt) bsk

≤ f (axk+ bskt) bsk

= f (1) bsk

where xk= (1 − bskt)/a > 0. The inequality follows by taking the limit as k goes to infinity.

v) For all t ≥ 0, f (t) = f (1)t.

By ii), it holds for t = 0. Let t > 0, then also the function ht(x) := f (tx) satisfies the hypothesis. Hence, by iv), for all x ≥ 0, ht(x) ≤ ht(1)x. Finally, by letting x = 1/t > 0, together with iv), we obtain

f (t) ≤ f (1)t = ht(1/t)t ≤ ht(1)(1/t)t = f (t).



Riferimenti

Documenti correlati

[r]

It is known (see for example Theorem 1.a.5 in Banach Spaces by Lindenstrauss and Tzafriri) that every infinite dimensional Banach space X contains a basic sequence {x n } n≥1

[r]

[r]

[r]

[r]

[r]

Si procede come nel caso p = 2 utilizzando il fatto che se un numero primo p divide un prodotto di due numeri, allora deve dividere almeno uno dei